Within Prison Walls. Thomas Mott Osborne (Journal of Political Economy, 1915)
This study of early capitalistic organizations has revealed much interesting information relative to the character and extent of these industrial forms in the Middle Ages. The Montan industry furnishes the illustration of the earli- est capitalistic organization. In the mediaeval period there existed Kartels and monopolies in the tin industry of Saxony, in the wholesale tin trade of Bohemia and Saxony, in the quicksilver trade, and in some other less important industries. The description of the manipulation of the quicksilver mines of Almaden by the Spanish government and the Idrian mines by the Austrian government is of special interest. At certain periods during the early centuries there existed a complete monopoly of this industry, a monopoly, which by the way, was duplicated during the first half of the nineteenth century, up to the time of the discovery of the cinnabar mines of California, by the London house of Rothschild's control of the quicksilver output. This extensive development of capitalistic organization during the Middle Ages is explained by the financial politics of the popes and the heads of states. The need for money and the financial dependence of church and state upon big capital forced upon them methods contrary to the business ethics of the day. In order to assure themselves of high incomes, church and state have often practiced an unscrupulous monopolistic price policy in business fields where they had the power. What Hermann Levy has proved for England under Elizabeth, James, and Charles-that regents directly acted the r6le of speculation-hungry promoters of capitalistic enterprises-this also holds for the continent at a much earlier date. In the " Holy Roman land of the German nation" the creation of monopolies under Charles V and Ferdinand I had developed considerably. The crown and the merchant worked hand in hand in the upbuilding of early capitalistic organization. The inclusion of facsimiles of various business documents of the periodcontracts, letters, statutes, plans, and agreements-is an interesting feature of this book. Within Prison Walls. By THOMAS MOTT OSBORNE. New York: D. Appleton & Co., I9I4. 8vo